2023
DOI: 10.1186/s12902-023-01387-2
|View full text |Cite
|
Sign up to set email alerts
|

Graves’ disease after exposure to the SARS-CoV-2 vaccine: a case report and review of the literature

Kai Takedani,
Masakazu Notsu,
Naoto Ishiai
et al.

Abstract: Background Autoimmune/inflammatory syndrome induced by adjuvants (ASIA) is characterized by immune system dysregulation after exposure to adjuvants, such as aluminum. Although cases of autoimmune thyroid diseases caused by ASIA have been reported, Graves' disease is one of the rarer diseases. There are some reports that vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) cause ASIA. Here, we describe a case of Graves’ disease following SARS-CoV-2 vaccination and a revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Autoimmune-related thyroid and renal case reports include that of Graves’ disease following the second dose of the Pfizer COVID-19 vaccine [ 143 ] and “rapidly progressive IgA nephropathy” following the third dose of the Moderna COVID-19 vaccine [ 144 ]. A 78-year-old woman developed IgG4-related sialadenitis and autoimmune pancreatitis following her second Pfizer COVID-19 vaccine, the authors concluded: “the use of mRNA vaccines requires more studies regarding their effects on the human immune system” [ 145 ] (p. 1550).…”
Section: Evidence Of ‘Spikeopathy’—spike Protein Pathogenicitymentioning
confidence: 99%
“…Autoimmune-related thyroid and renal case reports include that of Graves’ disease following the second dose of the Pfizer COVID-19 vaccine [ 143 ] and “rapidly progressive IgA nephropathy” following the third dose of the Moderna COVID-19 vaccine [ 144 ]. A 78-year-old woman developed IgG4-related sialadenitis and autoimmune pancreatitis following her second Pfizer COVID-19 vaccine, the authors concluded: “the use of mRNA vaccines requires more studies regarding their effects on the human immune system” [ 145 ] (p. 1550).…”
Section: Evidence Of ‘Spikeopathy’—spike Protein Pathogenicitymentioning
confidence: 99%
“…During the SARS-CoV-2 (COVID-19) pandemic, cases of Graves disease and subacute thyroiditis related to COVID-19 infection or vaccination were reported, presumably due to the immunogenic nature of COVID-19. [18][19][20] A retrospective study reported a 2-fold increase in the incidence of Graves disease in a Spanish hospital in 2020-2021 compared with the pre-COVID-19 years (2017-2019). 21…”
Section: Covid-19 and Hyperthyroidismmentioning
confidence: 99%
“…Despite substantial advancements and positive results from vaccine candidate trials, several challenges still exist. These challenges include potential adverse effects of vaccines, the need for an ultra-cold supply chain for mRNA vaccines, and the weak immunogenicity of recombinant antigens even with the presence of aluminum salts as adjuvants ( 75 ). Despite these obstacles, vaccines are still being delivered worldwide to prevent virus-related diseases ( 76 ).…”
Section: Probiotics In the Post-covid-19 Eramentioning
confidence: 99%